Percepción y uso del agua de lluvia por usuarios del centro poblado "El Dorado". Km 25 - carretera Iquitos-Nauta. Loreto. 2022 - Arroyo Davila, Erik Omar (2022)
The present subject specified as objective, to evaluate the perception, characteristics and forms of use of the resource, by the users of rainwater in the community of "El Dorado". Iquitos-Nauta runway. Loreto. 2022. It is a non-experimental, quantitative, cross-sectional investigation. With a convenience sample of 60 people residing in the study community. A survey was applied, for the interpretation of the results descriptive statistics were applied. The following conclusions were reached: we worked with 53.33% of men and 46.67% of women; These people reached a secondary level of education (63.33%), whose main occupation is agriculture (33.33%) and housewives (33.33%). The use of the dwelling is house-room (90%), they live in this locality for up to 20 years (46.67%). Regarding water resources, they use different sources to obtain water (stream, traditional wells, rainwater). The rainwater that is collected is used for domestic tasks (75%) and is based on the use of simple, unsophisticated systems. For intake as a drink, they boil the water before using it (95%). They need up to 40 liters/day to satisfy their needs, the unit of measure used is 20-liter buckets, in addition to depositing the water in them. They consider the months of July and August as the driest of the year. Regarding the environmental awareness of the inhabitants, the positive opinion stands out for the collection of rainwater and its use, likewise, the uses with the greatest of water involve water for irrigation of plants, household cleaning, personal hygiene and consumption; They are aware that the environment must be taken care of. As a group of community members, they fully help the community, manage and report not to pollute, in addition to caring for and recycling water, producing compost from organic material, including reforestation activities (100%).